The Effects Of Fiscal And Monetary Discipline On Budgetary Outcomes - Bilin Neyapti (Turkish Economic Association, 2003)
This paper extends the game-theoretic model of Von Hagen and Harden (1995) that analyzes the impact of fiscal discipline on budgetary outcomes.It analyzes the effects on budgetary outcomes of both fiscal and monetary discipline, which are evaluated with respect to the relevant institutional rules. The model predicts that while both inflation and budget deficits are negatively associated with fiscal discipline, they may be positively associated with monetary discipline, proxied by central bank independence. This result obtains due to optimizing agents who internalize the burden of spending: inflation. Although not conclusive due to data limitations, the empirical findings of the paper support these predictions.
Keywords: D73; E58; H61; H72; 330; Budget Deficits; Central Bank Independence; Fiscal Discipline; Inflation